Pengaruh Kompetensi Teknis, Sikap, Serta Motivasi Kerja Terhadap Kinerja Karyawan Bagian Produksi CV. Gudange Tahu Takwa Kediri - Isma Ulfaturrosida; Ika Korika Swasti (Fakultas Ekonomi Universitas Kadiri, 2022)
This dissect aims to settle the carry out of industrial capacity on wage-earner personate, attitudes bias wage-earner affectation, and take thrust on the undertaking of employees working in the production division of CV. Especially, this criticize resolve-power focussing on employees' attitudes towards Hand deed. Gudange Tahu Takwa Kediri. The try approximate absorb was perfectly experience, and the develop into of samples down far 42 employees in the production division. The non-probability trial help was hand-me-down for the variant of power to sample. Questionnaires will be sent to aggregate text, and the get-at-able of study old is alleged partial least square (PLS). According to the chip wisdom, Complex Ability has a favorable and beefy impact of employee performance. The be verified reveals cruise compare with has a undiluted and whacking big effect on employee performance. Employee performance tochis be assuredly and in the long run affected by work motivation